Análise do uso de suporte ventilatório em recém-nascidos pré-termo internados em unidade de terapia intensiva neonatal - Tassinari, Cadi Caroline da Rocha (2019)
Respiratory problems are the most common intercurrences in neonatal period, resulting from the immaturity of the respiratory system. Knowing this, preterm newborns require, more frequently, the use of ventilatory support. The need for ventilatory support in preterm newborns in neonatal period may favor the occurrence of short-term pulmonary changes. Therefore, in the long term, increases the risk of developing chronic lung disease. Although, this study aimed to verify the use of ventilatory support in preterm newborns admitted to the Santa Casa de Caridade Neonatal Intensive Care Unit of Alegrete, RS, from january 2016 to december 2017. Data were obtained from records of preterm newborns who used ventilatory support. Each information was recorded in EXCEL 2008 ®, thus forming a database. The search of the medical records was performed by the researcher. After a database was built, these were analyzed statistically. A total of 410 records were analyzed, which 188 (45.9%) of the preterm newborns used ventilatory support. The main type of ventilatory support that was used the most was continuous positive airway pressure (CPAP) (77.1%). Among the main problems due the use and type of ventilatory support, we point Bronchopulmonary Dysplasia and late sepsis the two big ones. Beside, noninvasive ventilatory support showed a lower risk for these complications. The main reason for the exchange of ventilatory support was late sepsis (14.9%). This study concluded that the main ventilatory support used in the unit was CPAP, and that the use of invasive ventilatory support is associated with the risk of developing complications such as late sepsis and bronchopulmonary dysplasia. In addition, the use of less invasive ventilatory support reduces the risk of complications that may affect the long-term health of preterm infants.